2021
DOI: 10.1002/jcop.22746
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well‐being and vulnerability related to problematic Internet use among university students with and without disabilities: A comparative study

Abstract: This study aims to observe whether people with disabilities experience problematic Internet use (PIU) like that of young people without disabilities; to relate PIU to psychological distress in young disabled people and to determine whether these problems are similar to or different from those experienced by young people without disabilities. The sample comprised 408 university students with disabilities and 1386 university students without disabilities from several Spanish universities. PIU was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Existing studies have found that physical exercise and internet use impact subjective well-being [ 5 , 6 ]. At the same time, compared with other age groups, youth groups participate in physical exercise and use the internet more frequently [ 7 , 8 ]. Therefore, it is time to explore the impact of physical activity and internet use on the subjective well-being of youth groups.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have found that physical exercise and internet use impact subjective well-being [ 5 , 6 ]. At the same time, compared with other age groups, youth groups participate in physical exercise and use the internet more frequently [ 7 , 8 ]. Therefore, it is time to explore the impact of physical activity and internet use on the subjective well-being of youth groups.…”
Section: Introductionmentioning
confidence: 99%